New evidence on national culture and bank capital structure - Haq, M.; Hu, D.; Faff, R.; Pathan, Md Shams Tabrize (ELSEVIER SCIENCE BV, 2018)
© 2017 Elsevier B.V. We examine the nature of impact of national culture on bank leverage using a broad sample of 1701 banks from 79 countries, over the period 2000–2013, i.e., 18,996 bank-year observations. We find that banks in countries with high individualism culture dimensions hold more leverage while, banks in countries with high uncertainty-avoidance, power distance, and long-term orientation have less leverage. Notably, bank size substantially moderates these cultural effects. Our findings are robust to endogeneity, and alternative proxies for the dependent and core explanatory variables.